The Effectiveness of the Problem Based Learning (PBL) Model Assisted by Flipbook Media on Improving the Learning Outcomes of Pancasila Education Grade 4 SDN 1 Datar - Putri, Fatikhah Aprilia; Santoso; Pratiwi, Ika Ari (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2025)
The research is based on the low learning outcomes of students caused by learning still using lecture methods and media that are less interesting. It is proven by the discovery at SDN 1 Datar that the learning outcomes of Pancasila Education for grade 4 students are still relatively low. This study aims to determine the effectiveness of the PBL model assisted by Flipbook media on improving the learning outcomes of Pancasila education in grade 4 SDN 1 Datar. This study uses a quantitative research method with One Group Pretest Posttest involving class IV totaling 34 students as a sample for 5 meetings. The results of the normality test of learning outcome data, namely Pretest 0.261 and Postest 0.119 (> 0.05), mean that the data is normally distributed. The results of the Paired Sample T-test showed a significance value of 0.000 < 0.05 meaning that Ho was rejected and Ha was accepted. The N-Gain test obtained an average N-Gain Score of 0.7661 in the high category. Based on the results of the study, it was shown that the PBL model assisted by Flipbook media was effective in improving the learning outcomes of Pancasila Education in grade 4 of SDN 1 Datar.